Early Preventive Intervention for Young Children With Sex Chromosome Trisomies (XXX, XXY, XYY): Supporting Social Cognitive Development Using a Neurocognitive Training Program Targeting Facial Emotion Understanding - Bouw, Nienke; Swaab, Hanna; van Rijn, Sophie (Frontiers in Psychiatry, 2022)
Background: Sex Chromosome Trisomies (SCT; XXX, XXY, XYY) are genetic conditions that are associated with increased risk for neurodevelopmental problems and psychopathology. There is a great need for early preventive intervention programs to optimize outcome, especially considering the increase in prenatal diagnoses due to recent advances in noninvasive prenatal screening. This study is the first to evaluate efficacy of a neurocognitive training in children with SCT. As social behavioral problems have been identified as among the key areas of vulnerability, it was targeted at improving a core aspect of social cognition, the understanding of social cues from facial expressions. Methods: Participants were 24 children with SCT and 18 typically developing children, aged 4-8 years old. Children with SCT were assigned to a training (n = 13) or waiting list (no-training) group (n = 11). Children in the training group completed a neurocognitive training program (The Transporters), aimed to increase understanding of facial emotions. Participants were tested before and after the training on facial emotion recognition and Theory of Mind abilities (NEPSY-II), and on social orienting (eyetracking paradigm). The SCT no-training group and typically developing control group were also assessed twice with the same time interval without any training. Feasibility of the training was evaluated with the Social Validity Questionnaire filled out by the parents and by children’s ratings on a Visual Analogue Scale. Results: The SCT training group improved significantly more than the SCT no-training and TD no-training group on facial emotion recognition (large effect size; ηp2 =.28), performing comparable to typical controls after completing the training program. There were no training effects on ToM abilities and social orienting. Both children and parents expressed satisfaction with the feasibility of the training. Conclusions: The significant improvement in facial emotion recognition, with large effect sizes, suggests that there are opportunities for positively supporting the development of social cognition in children with an extra X- or Y-chromosome, already at a very young age. This evidence based support is of great importance given the need for preventive and early training programs in children with SCT, aimed to minimize neurodevelopmental impact.